2022
DOI: 10.1126/sciadv.abo3625
|View full text |Cite
|
Sign up to set email alerts
|

Electro-mechanical coupling of KCNQ channels is a target of epilepsy-associated mutations and retigabine

Abstract: KCNQ2 and KCNQ3 form the M-channels that are important in regulating neuronal excitability. Inherited mutations that alter voltage-dependent gating of M-channels are associated with neonatal epilepsy. In the homolog KCNQ1 channel, two steps of voltage sensor activation lead to two functionally distinct open states, the intermediate-open (IO) and activated-open (AO), which define the gating, physiological, and pharmacological properties of KCNQ1. However, whether the M-channel shares the same mechanism is uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
(248 reference statements)
0
6
0
Order By: Relevance
“…(a) Sequence alignment of the S4–S5 linker, S5 and S6 helices of hK V 7 subtypes reveals overlap between putative AO‐state coupling residues and the reported interaction sites of compounds known to modulate hK V 7 channel function. Coupling residues are indicated in bold, black text (Hou et al, 2020; Yang et al, 2022). Residues that cannabidiol (CBD) interacts with (based on coarse‐grained (CG) simulations) are highlighted in green.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Sequence alignment of the S4–S5 linker, S5 and S6 helices of hK V 7 subtypes reveals overlap between putative AO‐state coupling residues and the reported interaction sites of compounds known to modulate hK V 7 channel function. Coupling residues are indicated in bold, black text (Hou et al, 2020; Yang et al, 2022). Residues that cannabidiol (CBD) interacts with (based on coarse‐grained (CG) simulations) are highlighted in green.…”
Section: Discussionmentioning
confidence: 99%
“…What underlying mechanisms may explain the effects of CBD we observe in our study? Recently, Yang et al (2022) determined conserved residues along the S4–S5 linker, S5 and S6 helices of hK V 7.2 and hK V 7.3 channels that made important contributions to the electromechanical coupling of the voltage‐sensing domain to the pore domain. Mutation of these putative coupling residues led to dysfunctional channels, some of which could be partially rescued by retigabine.…”
Section: Discussionmentioning
confidence: 99%
“…63 Yang et al developed a Xenopus oocyte model based on three patients carrying variants in KCNQ2, which were LOF variants determined by cellular electrophysiologic studies, and these patients showed a 90% reduction in seizures upon administration of retigabine. 64 Recently, a novel AED, SF0034, was approved for use in the United States. Its therapeutic mechanism is similar to that of retigabine, and the efficacy of this drug is 5-fold higher than that of retigabine; however, its side effects limit the clinical application of this drug.…”
Section: (Kcnq2)-related Epilepsymentioning
confidence: 99%
“… 74 EE and intellectual decline are GOF variants, and the use of retigabine eliminates the potassium channel electro‐mechanical (E‐M) caused by current disruption induced by KCNQ3 variant, thus leading to antiepileptic therapeutic effects. 64 However, the drug is still contraindicated in children due to its skin and retinal discoloration side effects.…”
Section: K V Channel‐related Genes and Epilepsymentioning
confidence: 99%
See 1 more Smart Citation